Red Hat Certified Engineer (RHCE) EX294 : Red Hat Ansible automation (LiveLessons (Indianapolis, Ind.), 2020)
"RHCE EX294 Complete Video Course covers all facets of the newly-updated RHCE exam. Instructor Sander van Vugt walks you through the topics using demos and labs to test the student's knowledge with real world scenarios. Each video lesson ends with a lab that provides an exercise so you can test your skills. Sander then provides a detailed solution to each lab, explaining how to solve for the exam objectives so you can get the experience you need to pass the test. Audio instruction throughout offers detailed explanations, tips, and configuration verifications. This engaging self-paced video training solution provides learners with more than 10 hours of video instruction from an expert trainer with more than 20 years of practical Linux teaching experience. Through the use of topic-focused instructional videos, you will gain an in-depth understanding of all topics on the Red Hat Certified Engineer (RHCE) exam, as well as a deeper understanding of Red Hat Enterprise Linux and Ansible. The combination of video, labs, and practice exams provides a unique offering that gives you a full toolkit to learn and excel on your exam."--Resource description page